Online dissolved methane and total dissolved sulfide measurement in sewers. (1st January 2015) - Liu, Yiwen; Sharma, Keshab R.; Fluggen, Markus; O'Halloran, Kelly; Murthy, Sudhir; Yuan, Zhiguo
Abstract: Recent studies using short-term manual sampling of sewage followed by off-line laboratory gas chromatography (GC) measurement have shown that a substantial amount of dissolved methane is produced in sewer systems. However, only limited data has been acquired to date due to the low frequency and short span of this method, which cannot capture the dynamic variations of in-sewer dissolved methane concentrations. In this study, a newly developed online measuring device was used to monitor dissolved methane concentrations at the end of a rising main sewer network, over two periods of three weeks each, in summer and early winter, respectively. This device uses an online gas-phase methane sensor to measure methane under equilibrium conditions after being stripped from the sewage. The data are then converted to liquid-phase methane concentrations according to Henry's Law. The detection limit and range are suitable for sewer application and can be adjusted by varying the ratio of liquid-to-gas phase volume settings. The measurement presented good linearity ( R 2  > 0.95) during field application, when compared to off-line measurements. The overall data set showed a wide variation in dissolved methane concentration of 5–15 mg/L in summer and 3.5–12 mg/L in winter, resulting in a significant average daily production of 24.6 and 19.0 kg-CH4 /d, respectively, from the network with a daily average sewage flow of 2840 m 3 /day. The dissolved methane concentration demonstrated a clear diurnal pattern coinciding with flow and sulfide fluctuation, implying a relationship with the wastewater hydraulic retention time (HRT). The total dissolved sulfide (TDS) concentration in sewers can be determined simultaneously with the same principle. Graphical abstract: Highlights: A new online device was developed for dissolved CH4 and sulfide measurement in sewers. Field applications demonstrated its suitability for sewer applications. Continuous measurements revealed significant CH4 production in rising main sewers. Methane production in sewers is highly dynamic with a clearly visible diurnal pattern. Methane production in sewers also has a seasonal variation.